Distance Education and Remote Teaching: opposition by the vertex - Veloso, Braian (2022)
During the pandemic, was adopted, despite some terminological differences, the Remote Learning (RL), opposing it to Distance Education (DE). Thus, in this essay, we aim to evaluate the apparent distinctions, problematizing them. We conclude that the efforts aimed at diametrically separating the two realities are, in many ways, mistaken. We defend, in this light, that RL, if one wants to preserve its emergency dimension, is a variation of DE, as it comprises, as a foundation, the separation in space and/or time between the subjects, as well the use of technologies that enable pedagogical mediation.